The culture of data use in the management structures of a rural health district in the Western Cape Province - Hurter, Theunis (Department of Public Health and Family Medicine, 2015)
Background: Health information system (HIS) performance has been defined as â€œdata quality and the continuous use of information â€ . The quality of data, as well as the culture of data use in an organisation has been shown to shape the way data is used. In order to fully understand data use practices with the aim of strengthening the HIS, one needs to first understand whether the context and â€œcultureâ€ in the organisation is conducive to data use. Are the policies, structures, processes and people within the organisation aiding data use? In what ways do managers view and use data? Aim: In this study, we sought to explore the culture of health information use on a district and sub district management level. The aim was to contribute to the wider knowledge on information use by exploring the data use practices and factors that shape its use among these managers. What is the culture of data use in the district management structures? When, why and in what way does data get brought into the management discussion? Do managers feel that the information produced are useful in aiding their decision making, and what do they recommend be changed? What are the key factors that affect data use practices? Methods: This thesis comprises a literature review of published articles, conducted in order to provide context for the study of the culture of data use, whilst defining the problem to be investigated. The full thesis comprises the literature review, the original study protocol, a full manuscript in the format of a publishable article and a set of appendices. The study was granted ethical approval and permission from the provincial department of health. Given the exploratory purpose of the study, we conducted a mini ethnographic case study using qualitative research methods in a rural health district of the Western Cape Province of South Africa. The researcher employed ethnographic methods that included participant observation, in depth key informant interviews, document reviews as well as informal conversations to collect data. We used the PRISM framework as a guide for analysing our findings. Findings: Our findings suggest that there is a strong focus in this district on reporting requirements and technical aspects of producing good quality data. The drive to achieve excellence in production of quality data may be in tension with another important organisational value, which is the need of managers, for ease of access to relevant data, to facilitate decision-making and improvement of health service delivery. Managersâ€™ overall experience is of not receiving the health information support they require. Instead, they experienced an organisational culture of using health information to narrowly measure targets and performance, which left them feeling unsupported and frustrated. Managers were resilient in managing these challenges and created alternative ways of accessing the data they needed for decision-making. Conclusion: We conclude that in our setting where the technical component of producing good data was well performed, this was not sufficient to guarantee effective use of data for quality improvements. Behavioural and organisational factors were found to play an important role as both obstacles and facilitators in shaping the culture of data use, information that is useful to inform design of interventions for health information strengthening.